2015
DOI: 10.1007/s10695-015-0140-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diets enriched with rutin on blood parameters, oxidative biomarkers and pituitary hormone expression in silver catfish (Rhamdia quelen)

Abstract: The effects of adding rutin to the diet (0, 0.15 or 0.30%) of silver catfish for 21 days on blood parameters, oxidative stress biomarkers and pituitary hormones expression were investigated. Fish that received the diet containing 0.15% rutin exhibited reduced plasma cortisol levels. The levels of lipid peroxidation were lowered in the all tissues of animals receiving the diet containing rutin. Rutin increased the activity of the superoxide dismutase (SOD), catalase (CAT), nonprotein thiols (NPSH), ascorbic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 48 publications
3
19
1
Order By: Relevance
“…However, gilthead sea bream fed with 2.0 ml of EOMS showed a reduction in the plasma levels of cortisol. Similar results were found in R. quelen and Paralichthys olivaceus fed with diets containing rutin (Pês, Saccol, Ourique, Londero, Gressler, Finamor et al., ) and quercetin (Shin, Yoo, Min, Lee, & Choi, ), respectively, both compounds considered as important antioxidants. Regarding the effects of EOs, several studies have shown that these substances act as anaesthetics and prevent an increase in plasma cortisol levels in different fish species, supposedly blocking sensorial transmission to the hypothalamus, as well as the subsequent triggering of the hormonal cascade (Gressler et al., ; Iversen, Finstad, McKinley, & Eliassen, ; Saccol, Londero et al., ; Saccol, Toni et al., ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…However, gilthead sea bream fed with 2.0 ml of EOMS showed a reduction in the plasma levels of cortisol. Similar results were found in R. quelen and Paralichthys olivaceus fed with diets containing rutin (Pês, Saccol, Ourique, Londero, Gressler, Finamor et al., ) and quercetin (Shin, Yoo, Min, Lee, & Choi, ), respectively, both compounds considered as important antioxidants. Regarding the effects of EOs, several studies have shown that these substances act as anaesthetics and prevent an increase in plasma cortisol levels in different fish species, supposedly blocking sensorial transmission to the hypothalamus, as well as the subsequent triggering of the hormonal cascade (Gressler et al., ; Iversen, Finstad, McKinley, & Eliassen, ; Saccol, Londero et al., ; Saccol, Toni et al., ).…”
Section: Discussionsupporting
confidence: 75%
“…Plant‐derived substances have been employed as functional feed supplements for commercial fish to improve growth performance (Acar, Kesbiç, Yilmaz, Gültepe, & Türker, ; Giri et al., ; Zeppenfeld et al., ; Zheng et al., ), antioxidant activity (Pês, Saccol, Ourique, Londero, Gressler, Finamor et al., ; Pês, Saccol, Ourique, Londero, Gressler, Golombieski et al., ; Saccol et al., ) and storage and to produce a delay in the deterioration of fillets (Álvarez, García, Jordan, Martínez‐Conesa, & Hernández, ), thereby not only improving fish health but also increasing productivity and the value of the commercial product produced. Our results reveal that the inclusion of EOMS in feed did not affect growth rates after 90 days of experimentation, which has been also shown by Saccol et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, there has been a growing interest in alternatives to improve production without affecting the environment. The use of medicinal plants and their major compounds as dietary additives has attracted much attention worldwide and has been the subject of several studies, assisting in the control of diseases, improving growth, and as immunostimulant (Bandeira Jr. et al, ; Pês et al, ; Saccol et al, ; Souza et al, ; Zeppenfeld et al, ).…”
Section: Introductionmentioning
confidence: 99%